Numerical Investigation of All-Optical Forward-Error-Correction Coding Scheme With Convolutional Code - Yohei Aikawa; Hiroyuki Uenohara (IEEE Photonics Journal)
In this paper, we propose an optical forward-error-correction (FEC) coding scheme with convolutional code using four-wave mixing (FWM) in a highly nonlinear fiber (HNLF) to realize an adaptive coding scheme corresponding to the signal-to-noise ratio (SNR) between nodes in photonic networks. The performance of the proposed scheme was numerically investigated for $2^{11}-1$ pseudorandom bit sequence (PRBS) differential phase-shift keying (DPSK) modulated return-to-zero (RZ) format signals at 10 Gb/s. The optimized condition of optical xor operations, which are the main components of the target coding scheme, is obtained for fiber length, signal wavelengths, and signal powers. Based on the optimized condition, the power penalties of the FEC coding scheme achieved are approximately 0.5 and −0.8 dB at $\text{BER}=10^{-9}$ in the cases of two- and three-input optical xor operations, respectively, indicating that the proposed scheme obtains a net coding gain. The high-quality coded signals, which keep 5-dB degradation of the $Q$ -factor from its maximum value of 40, are achieved with the 6.1- and 6.2-dB input power tolerances for coded signals 1 and 2, respectively.